2020
DOI: 10.7759/cureus.8061
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Radiological Features of Patients With Pulmonary Cryptococcosis in a Hospital of North China

Abstract: Objective: The increasing incidence has led to more focus on pulmonary cryptococcosis in HIVnegative patients. We conducted a retrospective analysis of pulmonary cryptococcosis to understand the clinical characteristics, imaging features, diagnosis, treatment and prognosis of this disease in HIV-negative patients in respiratory department of a tertiary hospital in north China. Method: We identified retrospectively those diagnosed with pulmonary cryptococcosis in the first medical center of Chinese People's Lib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 16 publications
1
3
1
Order By: Relevance
“…We also observed no obvious inflammatory reaction or lymphocyte infiltration in the lesions under the microscope, which Zinck et al mentioned in the article 19 . This study found that the number of multiple lesions, air bronchial sign and cavitation were more common in immunocompromised patients, which was consistent with the results of previous literature studies 20 22 . Xie et al reported that air bronchial signs are common in immunocompromised patients with PC 23 .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…We also observed no obvious inflammatory reaction or lymphocyte infiltration in the lesions under the microscope, which Zinck et al mentioned in the article 19 . This study found that the number of multiple lesions, air bronchial sign and cavitation were more common in immunocompromised patients, which was consistent with the results of previous literature studies 20 22 . Xie et al reported that air bronchial signs are common in immunocompromised patients with PC 23 .…”
Section: Discussionsupporting
confidence: 93%
“…Cryptococcus is commonly found in bird feces and soil 11 , 12 , and it appears that immunocompromised patients and people with a history of environmental exposure are more susceptible to infection. A growing body of literature now points out that it is more common in normal people with no history of exposure 13 , 14 . A total of 8.8% of the patients in the study had a history of environmental exposure, and 61.8% of the patients were in the normal population.…”
Section: Discussionmentioning
confidence: 99%
“…While nodules have been reported as the most common radiological feature of PC ( 1 , 21 , 27 ), we found that pneumonia was more common in the chest CT scans of our PC patients. This difference may be due to a large number of asymptomatic patients who found nodules during health checkups but did not undergo further examinations for Cryptococcus, opting instead for follow-up.…”
Section: Discussioncontrasting
confidence: 55%
“…This also explains why percutaneous lung biopsy is used in most pathological examinations, and the positive rate of percutaneous lung biopsy (90.0%) is much higher than that of TBLB (46.1%). These are closely related to the characteristics of cryptocosis in which the lesions are mostly located in subpleural [12,16,27,28].…”
Section: Discussionmentioning
confidence: 91%